Effect of Hospital Employees’ Psychological Capital on Counterproductive Work Behavior: Role of Work Alienation and Procrastination - Ayşe Göksu Özüdoğru G.; Görener A.; Toker K. (My University, 2024)
Counterproductive work behavior (CWB) causes financial losses and psychologically affects other employees exposed to verbal or physical attacks from their colleagues. This issue creates a stressful workplace and has a negative impact on organizational outputs. The objective of this study is to develop a coherent logic and a thorough comprehension of the CWB’s predecessors and their relationships to the CWB. Our research applied partial least squares structural equation modeling (PLS-SEM) to test hypotheses on a sample of 390 healthcare personnel in a hospital. We propose an approach in which administrators can reduce counterproductive work behaviors by strengthening psychological capital. Also, eliminating work alienation and workplace procrastination is an original and critical argument for preventing counterproductive work behavior. The findings reveal that high psychological capital negatively affected counterproductive work behaviors and reduced these behaviors in the workplace. However, the partial mediation role of work alienation and the mediation role of workplace procrastination were determined in the relationship between psychological capital and counterproductive work behavior
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Yönetim ve Organizasyon; Sağlık Yönetimi; İnsan Kaynakları Yönetimi; İşletme Yönetimi; Sağlık Bilimleri; Social Sciences and Humanities; Management; Management and Organization; Health Management; Human Resources Management; Management of Enterprises; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Ekonomi ve İş; YÖNETİM; İŞLETME; Clinical Medicine (MED); Social Sciences (SOC); ECONOMICS & BUSINESS; MANAGEMENT; BUSINESS; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities